Genotype × environment interaction for the agronomic performance of high β-carotene sweetpotato - Otoboni, M.E.F.; Oliveira, D.J.D.; Pavan, B.E.; Andrade, M.I.; Vargas, P.F. (Universidade Estadual de Maringa, 2022)
Sweetpotato (Ipomoea batatas L.) is an important tuber vegetable for human health worldwide owing to its nutritional value and productivity. Consumption of orange-fleshed sweetpotato is beneficial to combat vitamin A deficiency in the world, including Brazil, as these tubers are rich in beta-carotene, a precursor of vitamin A. The genotype x environment interaction is one of the greatest challenges in plant breeding, specifically in the selection and approval of cultivars. In this context, adaptability and stability analyses are warranted to evaluate the performance of various genotypes in terms of general or specific adaptations to certain environments and to identify genotypes responsive to environmental variations. Thus, the objective of this study was to evaluate the genotype x environment interaction as well as to estimate the adaptability and stability of sweetpotato genotypes for identifying and selecting promising candidates for breeding. The experiments were performed in four environments: Vera Cruz in Sao Paulo, Selviria in Mato Grosso do Sul, and one organic and another intercropped production system in Sete Barras in Sao Paulo. A randomized block design with two replicates was adopted. A total of 265 genotypes were tested, and the orange-fleshed sweetpotato cultivar 'Beauregard' was used as the control. The additive main effects and multiplicative interaction model was used to study environmental stratification, adaptability, and stability. The genotype x environment interaction was evident in all environments. The genotypes CERAT21-13 (marketable root yield, 22.30 t ha(-1) in the four environments), CERAT29-26 (27.74 t ha(-1)), and CERAT52-22 (20.24 t ha(-1)) were the most adapted in general to the four environments. CERAT25-23, CERAT29-23, and CERAT29-26 were the most adapted to the environment in Vera Cruz; CERAT29-26, CERAT34-14, and CERAT56-32 to the environment in Selviria; and CERAT31-10, CERAT35-19, and CERAT52-22 to the two environments in Sete Barras.